Factors controlling gas turbine combustion performance at high pressure - Lefebvre, Arthur H. (Cranfield College of Aeronautics, 1965)
In the post most of the research work carried out in gas turbine combustion was mainly concerned with performance problems arising at high altitudes. these were primarily problems of trying to achieve high combustion efficiency, adequate stability and good relighting performance. This research necessitated the use of expensive test facilities to provide large quantities of air at sub atmospheric pressure. For this reason much effort was expended in trying to find methods of simulating low combustion pressures, and in the development of correlating parameters which would allow low pressure performance to be predicted from experimental data obtained at more convenient levels of pressure. In recent years, however, there has been a marked trend towards engines of higher compression ratio. This is illustrated in figure 1 which was reproduce& from a paper by Pearson. This trend has not produced any new problems, with the possible exception of exhaust smoke, but it has aggravated many problems which previously caused no great concern, and it has exposed many deficiencies in our knowledge of certain basic processes, particularly those affecting combustion and heat transfer at high pressure. One object of this paper is to examine the influence of pressure on various aspects of combustion performance. Another object is to derive formulae from which the influence of increasing pressure on various performance criteria can be estimated. One important effect arising at high pressures is an increased dependence of all aspects of combustion performance on fuel spray characteristics. Because of their importance and because so far they appear to have received comparatively little attention, much of this paper is devoted to the effect of pressure on various spray properties such as penetration, droplet size and cone angle.